Cellulose Chemistry and Properties: Fibers, Nanocelluloses and Advanced Materials - Rojas, Orlando J. (Advances in Polymer Science, 2016)
Vincent Bulone et al.: Cellulose sources and new understanding of synthesis in plants Thomas Heinze et al.:Cellulose structure and properties Thomas Rosenau, Antje Potthast, Ute Henniges et al.: Recent developments in cellulose aging (degradation / yellowing / chromophore formation) Sunkyu Park et al.:Cellulose crystallinity Lina Zhang et al.:Gelation and dissolution behavior of cellulose Yoshiyuki Nishio et al.:Cellulose and derivatives in liquid crystals Alessandro Gandini, Naceur Belgacem et al.:The surface and in-depth modification of cellulose fibers Emily D. Cranston et al.:Interfacial properties of cellulose  Herbert Sixta, Michael Hummel et al.Cellulose Fibers Regenerated from Cellulose Solutions in Ionic Liquids Qi Zhou et al.:Cellulose-based biocomposites  Orlando Rojas et al.:Films of cellulose nanocrystals and nanofibrils  Pedro Fardim et al.:Functional cellulose particles Wadood Hamad et al.:Cellulose Composites.